Institutions, Culture, and Wetland Values - Mayula Chaikumbung; Chris Doucouliagos; Helen Scarborough (Institute of Labor Economics (IZA), 2018)
Do institutions and culture affect environmental values? In this article we analyze 1,041 environmental valuations of 223 wetlands in 38 developing countries, to examine the effect of institutions and culture on environmental values. We assess three dimensions of institutional quality: economic freedom, democracy, and good governance. We also consider the impact of cultural differences. Possibly surprisingly, wetland values are lower in more market based economies and they are lower in cultures that are more indulgent and authoritarian. In contrast, improved government effectiveness increases wetland valuations. Understanding these important and varying effects of institutions and culture on wetland valuations is important for policy development and environmental preservation.
Keywords: Q3; H4; O13; P48; 330; institutions; culture; wetlands; valuations; environmental preferences; meta-regression